On the 𝑞-Bernoulli Numbers and Polynomials with Weight 𝜶 - T. Kim; J. Choi (Abstract and Applied Analysis)
We present a systemic study of some families of higher-order 𝑞-Bernoulli numbers and polynomials with weight 𝛼. From these studies, we derive some interesting identities on the 𝑞-Bernoulli numbers and polynomials with weight 𝛼.